2015
DOI: 10.1016/j.biopsych.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Secretase-Activating Protein Is a Substrate for Caspase-3: Implications for Alzheimer’s Disease

Abstract: SUMMARY Background A major hallmark feature of Alzheimer’s disease (AD) is the accumulation of amyloid β (Aβ), whose formation is regulated by the γ-secretase complex and its activating protein (also known as GSAP). Because GSAP interacts with the γ-secretase without affecting the cleavage of Notch, it is an ideal target for a viable anti-Aβ therapy. However, despite much interest in this protein, the mechanisms involved in its neurobiology are not known. Methods Post-mortem brain tissues from AD patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 23 publications
0
53
0
Order By: Relevance
“…The discrepancy in 16 kDa GSAP levels between DS and AD (present findings) could be related to the presence of an extra copy of the APP gene in DS that might stimulate the expression of GSAP or other confounding components such as transcription factors [9, 22]. Data indicate that formation of the 16 kDa GSAP active form depends on caspase-3 [9], an apoptotic marker that is elevated and highly expressed in neurofibrillary tangles and plaques, in both human AD and animal models of this disease [21]. Although previous investigations indicate that 16 kDa GSAP levels are associated with Aβ deposition [5, 6], here we found that GSAP protein levels did not correlate with amyloid and NFT scores either in the frontal cortex or hippocampus across clinical groups.…”
Section: Discussionmentioning
confidence: 97%
“…The discrepancy in 16 kDa GSAP levels between DS and AD (present findings) could be related to the presence of an extra copy of the APP gene in DS that might stimulate the expression of GSAP or other confounding components such as transcription factors [9, 22]. Data indicate that formation of the 16 kDa GSAP active form depends on caspase-3 [9], an apoptotic marker that is elevated and highly expressed in neurofibrillary tangles and plaques, in both human AD and animal models of this disease [21]. Although previous investigations indicate that 16 kDa GSAP levels are associated with Aβ deposition [5, 6], here we found that GSAP protein levels did not correlate with amyloid and NFT scores either in the frontal cortex or hippocampus across clinical groups.…”
Section: Discussionmentioning
confidence: 97%
“…Cell immunostaining was carried out as previously described (Chu et al ., 2015). Briefly, after treatment, N2A‐APPswe cells were plated on glass coverslips, and the following day, fixed in 4% paraformaldehyde in PBS for 15 min at 22 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of their excellent AChEinhibition capacity, the above drugs have serious side effects such as Nausea, vomiting, diarrhea, weight loss, loss of appetite and muscle weakness. 3,18 Many other plant compounds have shown remarkable AChE inhibitory capacity, for example, withanolides from Withania somnifera Dunal. (ashwaganda or Indian ginseng), cur cuminoids from Curcuma longa L., tanshinones from Salvia miltiorrhiza Bunge and quercetin from Quercus sp.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Because of the absence of a permanent cure, AD has become a major health problem, although there are some treatments that may slow down its advances. 3 It is estimated that there are 35.6 million people living with dementia worldwide and will increase to 65.7 million by 2030, whereby much of the increase will be in developing countries. 4 Neurofibrillary tangles, Amyloid plaques and loss of cholinergic neurons are three pathological findings commonly observed in the cerebral cortex of Alzheimer's disease cases.…”
Section: Introductionmentioning
confidence: 99%